(:unas) unassigned - Chrysostomou, Christis (My University, 2020)
Duties included the coordination of the three Departments in the Faculty and the chairing of the School Board. As Dean I also participated in the Senate of the University, as well as the Senate Committees of a) Economics and Personnel, b) Strategic Planning and Development and c) Rules and Regulations.